Factors Affecting Decision Making Behavior on the Bridge Over the River Kwai Kanchanaburi - อาภรณ์พิศาล ชนพงษ์; ชัชวาลชาญชนกิจ เพ็ชราภรณ์; อาภรณ์พิศาล พรรณรัตน์ (Thai Interdisciplinary and Sustainability Review, 2021)
The objectives of this research are 1) to study tourism factor levels. And the decision to visit the bridge over the River Kwai Kanchanaburi 2) to study the factors of tourism components affecting the decision to visit the bridge over the River Kwai. Kanchanaburi The quantitative research method was used 1) The opinion level of tourism factors in overall and in each aspect was at a high level. And the decision to travel in the whole and each item was at a high level as well. Kanchanaburi province is the area of ​​attraction (X1), accommodation (X4), access (X2), facilities (X3) and activities (X5) by writing the equation for predicting the decision to visit the bridge over the River Kwai as follows: tot= .483 +.244(X1)+.227(X4)+.212(X2)+.189(X3)+.146(X5)